1985
DOI: 10.1029/rs020i006p01309
|View full text |Cite
|
Sign up to set email alerts
|

On observation of gravity wave spectra in the atmosphere by using MST radars

Abstract: Recently, gravity waves and two-dimensional turbulence have been proposed as possible causes for the observed mesoscale wind fluctuations in the atmosphere. In order to use wind velocity data measured by MST radars to investigate atmospheric gravity wave spectra, it is important to apply the correct relation between the observed wind fluctuation spectrum and the wave spectrum. In this paper, based on acoustic-gravity wave theory and radar observation principle, this relationship is quantitatively derived for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…Figure 6 reveals that the derived spectral slopes under active conditions (left panel) follow a roughly symmetric distribution around a mean of ∼ −5/3 with minimum and maximum values between −8/3 and −2/3. This is consistent with theory and previous studies (e.g., Scheffler and Liu, 1985;Ecklund et al, 1985;Gage et al, 1986). Under quiet conditions (right panel), however, the spectral slopes follow a very asymmetric distribution with a long tail extending towards smaller values with a maximum at around −10/9, which is close to −1.…”
Section: Resultssupporting
confidence: 81%
“…Figure 6 reveals that the derived spectral slopes under active conditions (left panel) follow a roughly symmetric distribution around a mean of ∼ −5/3 with minimum and maximum values between −8/3 and −2/3. This is consistent with theory and previous studies (e.g., Scheffler and Liu, 1985;Ecklund et al, 1985;Gage et al, 1986). Under quiet conditions (right panel), however, the spectral slopes follow a very asymmetric distribution with a long tail extending towards smaller values with a maximum at around −10/9, which is close to −1.…”
Section: Resultssupporting
confidence: 81%
“…1 show a typical pattern with a peak at the Brunt-Vaisala frequency (Röttger, 1986;Scheffler and Liu, 1985), a steep decrease in amplitude in the high frequency side, and a fairly shallow decrease in amplitude in the low frequency side. Based on earlier studies by Röttger (1986), developed a method for determining tropospheric and lower stratospheric temperature from MST radar observations of vertical wind.…”
Section: Evaluation Of Temperaturementioning
confidence: 99%
“…By closely following the procedure in Scheffler and Liu [1985], the observed velocity fluctuation along the beam direction is found to be…”
Section: Gravity Wave Spectra and Variances Observed By Radarmentioning
confidence: 99%
“…Recently, MST radars have been used by many investigators to study the spectra of velocity fluctuations in the middle atmosphere [Balsley and Carter, 1982;Meek et al, 1985;Scheffler and Liu, 1985;Scheffler and Liu, 1986;Smith et al, 1985;Franke et al, 1988, VanZandt, 1985. Attempts have been made by these authors to interpret the observed spectra in terms of internal gravity waves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation